2001
DOI: 10.1051/0004-6361:20000493
|View full text |Cite
|
Sign up to set email alerts
|

A photometric study of the W UMa-type system U Pegasi

Abstract: Abstract. In the present study, the activity of the eclipsing binary of the W UMa-type system U Peg is examined by analysing the photoelectric observations covering the period from 1950 to 1989. During this period, the light curves show significant differences and asymmetries. The analysis of the corresponding light curves is made using Djurašević's inverse problem method. To explain the light-curve asymmetries and variations, we used a Roche model that involved regions containing spots on the components. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“… References: (1) Gazeas et al (2005); (2) Zoła et al (2005); (3) Gazeas & Niarchos (2006); (4) Terrell et al (2006);(5) Yang, Qian & Zhu (2005); (6) Zhang & Zhang (2004); (7) Yakut et al (2005); (8) Qian et al (2005); (9) Lu, Hrivnak & Rush (2007), (10) Szalai et al (2007); (11) Lu (1991); (12) Zhang, Zhang & Deng (2005); (13) Özdemir et al (2002); (14) Djurašević et al (2001). …”
Section: Status Of W Uma Systemsmentioning
confidence: 99%
“… References: (1) Gazeas et al (2005); (2) Zoła et al (2005); (3) Gazeas & Niarchos (2006); (4) Terrell et al (2006);(5) Yang, Qian & Zhu (2005); (6) Zhang & Zhang (2004); (7) Yakut et al (2005); (8) Qian et al (2005); (9) Lu, Hrivnak & Rush (2007), (10) Szalai et al (2007); (11) Lu (1991); (12) Zhang, Zhang & Deng (2005); (13) Özdemir et al (2002); (14) Djurašević et al (2001). …”
Section: Status Of W Uma Systemsmentioning
confidence: 99%
“…In a recent study, Djurašević et al (2001) investigated the long term photometric variations of the system over the time interval of 1950 to 1989. They concluded that the complex variations of the light-curves during these four decades can be explained by the variable spot activity of the cooler component.…”
Section: U Pegasimentioning
confidence: 99%
“…In fact, spot activity derived from the light curves of several observing seasons and the corresponding magnetic activity also appear in many other W UMa binary stars, such as AU Ser (Gürol 2005), U Peg (Djurašević et al 2001), AD Cnc (Qian et al 2007), FG Hya (Qian & Yang 2005) and CE Leo (Yang & Liu 2002b).…”
Section: Discussionmentioning
confidence: 91%